Homelessness, HIV testing, and the reach of public health efforts for people who inject drugs, San Francisco, California. (1st April 2021) - Vincent, Wilson; Lin, Jess; Veloso, Danielle; Miller, Desmond; McFarland, Willi
Highlights: Living in single-room occupancy hotels was associated with getting HIV tested. Living with others was associated with sharing syringes but not HIV testing. Living outdoors was associated with sharing syringes but not HIV testing. Younger people who inject drugs (PWID) were less stably housed than older PWID. Public health and HIV screening efforts may not be reaching unstably housed PWID. Abstract: Background: There is a dearth of literature that explicitly examines associations between housing and HIV testing among people who inject drugs (PWID). Thus, the present study investigated the links between housing status and HIV testing for PWID. Methods: Respondent-driven sampling recruited 382 HIV-negative PWID, who completed structured interviews in San Francisco. Logistic regression determined whether housing statuses in the past 12 months ([1] owned/rented, [2] single-room occupancy hotels [SROs], [3] living with friends/family/partners, [4] shelters, [5] outdoors) were associated with getting HIV tested in the past 12 months while adjusting for sociodemographics and receptive sharing of injection paraphernalia in the past 12 months. Results: PWID who lived in SROs had greater odds of being tested for HIV than PWID who did not live in SROs ( aOR = 1.95, CI.95 : 1.06–3.60) while adjusting for covariates. Although bivariable analyses indicated that receptively sharing syringes was more common for PWID who lived with others (χ 2 [3] = 7.94, p = 0.047) or lived outdoors (χ 2 [3] = 9.50, p = 0.023) than those who did not, respectively, PWID who lived with others ( aOR = 1.72, CI.95 = 0.95–3.14) or lived outdoors ( aOR = 1.37, CI.95 = 0.74–2.53) did not show greater odds of HIV testing in multivariable analyses. Conclusions: PWID who lived in SROs had greater odds of HIV testing than PWID who did not live in SROs. Although PWID who lived with others or outdoors showed greater HIV risk, they did not show greater odds of HIV testing. Public health efforts may be reaching PWID in SROs, but more work is needed to reach PWID who live with other people or outdoors.